Dynamics of scientific development in dakwah education Indonesia - Aep Kusnawan; Nanih Machendrawaty (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This study aims to determine the efforts from time to time of scientists in da'wah educational institutions in Indonesia that diligently carry out studies and publications. This research is also expected to avoid disconnection in understanding the history of Da'wah science.Method - This research was conducted through a literature review, with a historical approach. Where several references related to Da'wah scholarship are classified, discussed, and concluded.Result - The results show that the dynamics of scientific development in da'wah education in Indonesia have shown a dynamic history. The dynamism is illustrated by the alternation of da'wah scientific activities carried out and carries a sustainable theme from time to time. Another dynamic is evident in the productivity of the work they write and publish, both in the form of journals and books. The two aspects become one strength so that in its development, it further strengthens the science of Da'wah. As well as being an example for future generations to have enthusiasm and productivity that is more or less like them.Implication - this paper suggests the development of da’wah science that allows correction, addition, and perfection from the development of new science.Originality - This article is a study that shows the transformation from da'wah to da'wah science.***Tujuan - Penelitian ini bertujuan untuk mengetahui upaya dari waktu ke waktu para ilmuwan di lembaga pendidikan dakwah di Indonesia yang rajin melakukan kajian dan publikasi. Penelitian ini juga diharapkan dapat menghindari keterputusan dalam memahami sejarah ilmu dakwah.Metode - Penelitian ini dilakukan melalui studi pustaka, dengan pendekatan sejarah. Dimana beberapa referensi terkait keilmuan Dakwah diklasifikasikan, dibahas, dan disimpulkan.Hasil - Hasil penelitian menunjukkan bahwa dinamika perkembangan keilmuan dalam pendidikan dakwah di Indonesia, telah menunjukkan sejarah yang dinamis. Kedinamisan tersebut tergambar dari silih bergantinya kegiatan keilmuan dakwah yang dilakukan dan mengusung tema berkelanjutan dari waktu ke waktu. Dinamika lain terlihat pada produktivitas karya yang mereka tulis dan terbitkan, baik dalam bentuk jurnal maupun buku. Kedua aspek tersebut menjadi satu kekuatan sehingga dalam perkembangannya semakin memperkuat ilmu dakwah. Serta menjadi contoh bagi generasi penerus untuk memiliki semangat dan produktivitas yang kurang lebih seperti mereka.Implikasi - Artikel ini menyarankan pengembangan keilmuan dakwah yang memungkinkan adanya koreksi, penambahan dan penyempurnaan pengembangan ilmu baru.Orisinalitas - Artikel ini merupakan kajian yang menunjukkan transformasi dari dakwah ke ilmu dakwah.